The evaluation of the reflexive competence in critical reading, a social-formative approach (Orkopata. Revista de Lingüística, Literatura y Arte, 2022)
The absence of educational tools on the part of teachers to evaluate the reflective competence in critical reading in an integral way in elementary school students constitutes a fundamental piece in order to determine their achievements, opportunities and difficulties. Therefore, the design of an evaluation instrument under a social-formative approach makes it possible to fully assess the development of this competence in each of its indicators and domain levels, in such a way that they respond to the international demands of training in competences. To achieve this purpose, a documentary analysis was made, contrasted with the experience regarding the evaluative practice of critical reading in the area of ​​Spanish language; obtaining as a product the design of a rubric that meets the criteria of the social-formative approach, by allowing feedback, systematization and evaluation of the teaching processes in the development of reading skills.
Keywords: reflective competence; critical reading; social-formative evaluation